Math(Roots)

posted by .

sqrt(24)
*I don't really get this stuff.Can somebody please help me?

The square root of 24 is 4.898979485566356

I know that..lol,but it says not to use decimals.Here is an example they gave me.
Ex.sqrt(18)=sqrt(2*3*3)=3sqrt(2)

sqrt[24] = sqrt[4*2*3] =
sqrt[4]*sqrt[2]*sqrt[3]=
2*sqrt[2]*sqrt[3]

  • Math(Roots) -

    Square root of 66

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. radical equation

    2^x+20=15+3^x A)1 B)16 C)-5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the square …
  2. math calculus please help!

    l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
  3. math

    determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the …
  4. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  5. Math

    How do you find a square root of a number that's not a perfect square?
  6. MATH

    1/(X^-2Y)-1(XY^-2)=____ XY (square root of 84 - square root of 5.25) I don't understand the first equation. sqrt(84)=sqrt(4*21)=sqrt(16*5.25)=4sqrt(5.25) so sqrt(84)-sqrt(5.25)= 4sqrt(5.25)-sqrt(5.25)=3sqrt(5.25)
  7. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  8. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  9. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
  10. Algebra - sqrts

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …

More Similar Questions